PENGARUH EMPLOYEE COMFORT, MEKANISME KERJA, DAN LINGKUNGAN KERJA YANG DI MEDIASI OLEH BUDAYA KERJA TERHADAP LOYALITAS KARYAWAN DI WISATA CELOSIA KABUPATEN SEMARANG - Uddin, Adji Alaa; Violinda, Qristin; Damaputra, Fadjar (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to examine the influence of employee comfort, work mechanisms, and work environment mediated by organizational culture on employee loyalty at Wisata Celosia, Semarang Regency. The research adopts a quantitative approach using a survey method involving 112 respondents. Data were collected through online questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The findings indicate that employee comfort, work mechanisms, and the work environment significantly influence organizational culture. Furthermore, these three factors also directly affect employee loyalty. Based on these results, management is advised to foster positive social relationships among employees and between superiors and subordinates, establish open communication, and ensure a safe and healthy work environment. These efforts are crucial to creating a sense of comfort and strengthening a positive organizational culture within the company.